1975
DOI: 10.1007/bf01910122
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transformations of oligoarylenes

Abstract: Thermal transformations of oligoarylenes, relating to polymers with conjugate systems, have been investigated in air and in vacuo, depending on the molecular weight and degree of branching of the original material. The extreme character of the thermostability in air versus the M-n value of oligoarylene, and the possibility of increasing the thermal oxidative stability by enhancing the degree of branching have been explained by different intensities of intermolecular processes of dehydropolycondensation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This latter is an extra indication in favour of a higher reaction capacity of high-polymeric OA fractions in polycondensation structurisation processes in the initial period of heat treatment in air, in comparison with the low-polymeric fractions (ref. 15 for the initial product on the thermo-oxidative stability is, it seems, common to all polymers with a conjugation system. In work (ref.…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter is an extra indication in favour of a higher reaction capacity of high-polymeric OA fractions in polycondensation structurisation processes in the initial period of heat treatment in air, in comparison with the low-polymeric fractions (ref. 15 for the initial product on the thermo-oxidative stability is, it seems, common to all polymers with a conjugation system. In work (ref.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…It is also shown that, when evaluating the thermo-oxidative stability of OAs using the TGA method, one must take into account the rate of temperature rise, since it influences the degree of completion of the structure of the products formed at the intermediate stages of heat treatment (ref. 15), and also the resistance to further thermo-oxidation. All these features must be considered in a comparative evaluation of the thermal stability of various oligomers with a conjugation system.…”
Section: Thermal Propertiesmentioning
confidence: 99%